Regulating employees' health behaviors: The effects of personal health-related orientations on legitimacy perceptions of organizational programs and policies - Hannah Klautke; Hee Sun Park (International Journal of Business Science & Applied Management (IJBSAM), 2011)
The current study investigated individuals' responses and evaluations of worksite health programs and policies. Upper level undergraduates rated the legitimacy of policies and programs exerting low, moderate, or high level s of control over employees' health behaviors. The findings showed that individuals' nutrition orientations accelerated the decrease in legitimacy ratings that accompanied increased control over employee fitness and health risk appraisal. On the other hand , individuals' anti - smoking orientations slowed the decrease in legitimacy ratings that accompanied increased control over employee smoking behavior. Implications of the findings for job counselors and human resource personnel are discussed.
Keywords: 650; worksite; health; smoking; fitness; health risk appraisal